Effect of Dietary Rumen Protected Methionine and/or Choline Supplementation on Rumen Fermentation Characteristics and Productive Performance of Early Lactating Cows - Soltan, M.A.; Mujalli, A.M.; Mandour, M.A.; Abeer, M. El-Shinway (Pakistan Journal of Nutrition, 2012)
Sixty early lactating Holstein dairy cows were fed for 12 weeks on berseem hay and cereal grains based total mixed ration formulated with the MET content limited (40 g/day) to investigate the effect of supplementing rumen protected methionine (15 g/day) and/or choline (30 g/day) on rumen fermentation characteristics, productive performance and some blood serum parameters. Cows were allotted into four groups and fed on the basal diet without supplementation, supplemented by 15 g/day of RP-MET, 30 g of RP-CHOL or 15 g MET + 30 CHOL respectively. Average body weight was not significantly different among treatment, but cows fed on basal diet supplemented by both RP-MET and RP-CHOL was mobilizing less body tissue in the post-partum period. RP-MET improved (p